AN TINJAUAN HUKUM MUAMALAH TERHADAP JUAL BELI RUM DI KUALASIMPANG (STUDI ANALISIS FATWA MUI N0 4 TAHUN 2003 TENTANG STANDARISASI FATWA HALAL DAN QANUN N0 6 TAHUN 2014 TENTANG HUKUM JINAYAH) - Asnita, Dessy; Emelda, Dahliana; Fakhrurrazi (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study examines the persistent practice of rum trading in Kuala Simpang, despite its prohibition under MUI Fatwa No. 4 of 2003 on halal standards and Qanun Aceh No. 6 of 2014 on Jinayah Law. Rum is commonly utilized in food and beverage preparation, imparting a sweet flavor with minimal alcoholic content. The research aims to analyze the prevailing rum trade practices and their implications in light of these religious and legal frameworks. Data were collected through interviews with rum sellers and consumers. Findings indicate that rum remains widely traded in Kuala Simpang, where it is frequently incorporated into cakes and beverages. According to MUI Fatwa No. 4 of 2003, such practices are deemed haram (forbidden), as even trace amounts of alcohol render consumption impermissible. Additionally, Aceh’s Qanun No. 6 of 2014 classifies rum as khamar (intoxicants), prohibiting its trade under Jinayah Law. Thus, the ongoing rum trade in Kuala Simpang violates both Islamic jurisprudence and regional legal statutes in Aceh